Studi Nilai Kesesuaian Produk Berstandar SNI di Jawa Timur - H.M. Ismail (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This study aims to assess the suitability of the products of SNI in East Java; engage in activities that aim to assess the suitability of a product, process, management system, and/or competency standards or other provisions that have been assigned to the SNI products in East Java; harmony plans, processes, information, materials for making decisions, actions, results, analysis, and learning to support the main purpose of suitability assessment SNI products in East Java; know the obstacles and drivers of the suitability standard ISO products in East Java. This research approach is quantitative with survey method. Instruments used in the implementation of a questionnaire survey. The results of this study are as follows: (1) There are clear criteria in determining the SNI products, and information obtained by the parties concerned can be accessed easily, (2) In the third component of the survey, namely non-food products, food products, and public opinion, all states that stakeholders can participate in the development of SNI and open, (3) There is transparency in the development of SNI ranging from programming and formulation stage to the stage of establishment, (4) On average, respondents said that the stakeholders can manyalurkan interests and treated fair, (5) trading facility provided by the national government in order to standardize considered effective and relevant, (6) There is a connectedness in the development of national standardization. In the third component of the survey contained figure of 2.83 in non-food product components, 2,76 on the components of food products, and 2.89 on the components of public opinion; (7) national standardization program that also consider the public interest and also interest national was also considered by respondents to have dimensions of development; (8) An increasing Index Standard Suitability Test Items from the year 2008–2010, although the range in 2007–2008 has decreased; (9) Index Standard Product SuitabilityTest in East Java viewed from statistical data presented in general belong to the category of ” good”; (10) for products already in the survey, referring to the results of statistical data, it deserves to get the label of SNI from stakeholders.Keywords: Indonesian National Standard (SNI), standardization, suitability